Large cobblestone dams for natural flood management in wide peatland gullies - Adam Ryan Johnston; David Brown; Tim Allott; Salim Goudarzi; Martin Kay; David Milledge; Emma Shuttleworth; Tom Spencer; Martin Evans (Ecological Engineering, 2025)

A Multimedia Arsenic Exposure Assessment for the Hopi Tribe, AZ, USA - Adam C. Carl; Robert A. Canales; Jonathan E. Blohm; Lorencita Joshweseoma; Steven J. Hadeed; Jefferey L. Burgess; Robin B. Harris; Mary Kay O’Rourke (Exposure and Health, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Calcification increases carbon supply, photosynthesis, and growth in a globally distributed coccolithophore - Austin R. Grubb; Christopher T. Johns; Matthew G. Hayden; Adam V. Subhas; Kimberlee Thamatrakoln; Kay D. Bidle (Limnology and Oceanography, 2024)
Coccolithophores fix organic carbon and produce calcite plates (coccoliths) that ballast organic matter and facilitate carbon export. Photosynthesis consumes carbon dioxide, while calcification produces it, raising questions about whether coccolithophores are a net sink or source of carbon. We characterized the physiology of calcified and noncalcified (“naked”) phenotypes of Emiliania huxleyi (CCMP374) and investigated the relationship between calcification and photosynthesis across a gradient of light (25–2000 μ mol photons m −2 s −1 ) spanning the euphotic zone. Growth and photophysiological parameters increased with light until reaching a mid‐light (150 μ mol photons m −2 s −1 ) maximum for both phenotypes. Calcified cells were characterized by enhanced photophysiology and less photoinhibition. Further, enhanced bicarbonate transport in calcified cells led to higher rates of particulate organic carbon fixation and growth compared to naked cells at mid‐light to high light (150–2000 μ mol photons m −2 s −1 ). Coccolith production was similarly high at mid and high light, but the rate of coccolith shedding was >3‐fold lower at high‐light (1.2 vs. 0.35 coccoliths cell −1 h −1 ). The cellular mechanims(s) of this differential shedding remain unknown and underly light‐related controls on coccosphere maintenance. Our data suggest coccoliths shade cells at high light and that enhanced bicarbonate transport associated with calcification increases internal carbon supplies available for organic carbon fixation.

Beyond the local climate change uplift – The importance of changes in spatial structure on future fluvial flood risk in Great Britain - Paul Sayers; Adam Griffin; Jason Lowe; Dan Bernie; Sam Carr; Alison Kay; Lisa Stewart (Natural Hazards, 2024)
Widespread spatially coherent flood events can cause severe damage and disruption. Climate change has the potential to change the severity and frequency of such events. Despite this, assessment of future fluvial flood risk typically gives little to no consideration to potential changes in the spatial structure of future events. To understand the significance of this gap, climate model simulations are coupled with a national hydrological model to identify event spatially coherent present and future flood events. A statistical Empirical Copula is used to generate a large number of unseen events and linked to a national flood risk simulation model. The research finds that including changes in the spatial structure of flood events materially increases projected changes in risk when compared to conventional approaches based on local uplifts alone; increasing the projected change in Expected Annual Damage across Great Britain by a factor of ~ 1.5. The event-based approach is also shown to provide new insights into the extreme distribution fluvial risk including single event damage, damage seasons, and damage years. The results suggest the 1-in-100-year winter flood may increase from £1.3b to £2.1b, and the 1-in-100 year single event damage may rise from £1.1b today to £1.7b by the 2080s given a 4 °C rise in Global Mean Surface Temperature (assuming current adaptation policies continue and no population growth). Consequently, the findings suggest a much greater emphasis is needed on spatial ‘flood events’ if future risk is to be understood and adaptation responses appropriately framed. Graphical abstract

Peatland gully restoration with stone and timber dams (Kinder Plateau, UK) - Tim Howson; Martin Evans; Tim Allott; Emma Shuttleworth; Adam Johnston; Joe Rees; David Milledge; Donald Edokpa; Chris Lockyer; Martin Kay; Tom Spencer; David Brown; et al. (Ecological Engineering, 2023)

PK/PD and Bioanalytical Considerations of AAV-Based Gene Therapies: an IQ Consortium Industry Position Paper - Uma Kavita; Kefeng Sun; Manuela Braun; Wibke Lembke; Hardik Mody; John Kamerud; Tong-Yuan Yang; Inka V. Braun; Xiaodong Fang; Wei Gao; Swati Gupta; Magdalena Hofer; et al. (The AAPS Journal, 2023)

College squirrels gone wild? Using Sciurus carolinensis behavior to assess the ecosystem value of urban green spaces - Adam D. Kay; Michael T. Hughes; Maddie G. Ammend; Mckenzie R. Granger; Jake J. Hodge; Jamaal Mohamud; Ellie A. Romfoe; Halima Said; Liam Selden; Alex L. Welter; Justa L. Heinen-Kay (Urban Ecosystems, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Direct effects of climate change on productivity of European aquaculture - Alhambra Martínez Cubillo; João G. Ferreira; João Lencart-Silva; Nick G.H. Taylor; Adam Kennerley; James Guilder; Susan Kay; Pauline Kamermans (Aquaculture International, 2021)

Increased grassland arthropod production with mammalian herbivory and eutrophication: a test of mediation pathways - Eric M. Lind; Kimberly J. La Pierre; Eric W. Seabloom; Juan Alberti; Oscar Iribarne; Jennifer Firn; Daniel S. Gruner; Adam D. Kay; Jesus Pascal; Justin P. Wright; Louie Yang; Elizabeth T. Borer (Ecology, 2017)
Increases in nutrient availability and alterations to mammalian herbivore communities are a hallmark of the Anthropocene, with consequences for the primary producer communities in many ecosystems. While progress has advanced understanding of plant community responses to these perturbations, the consequences for energy flow to higher trophic levels in the form of secondary production are less well understood. We quantified arthropod biomass after manipulating soil nutrient availability and wild mammalian herbivory, using identical methods across 13 temperate grasslands. Of experimental increases in nitrogen, phosphorus, and potassium, only treatments including nitrogen resulted in significantly increased arthropod biomass. Wild mammalian herbivore removal had a marginal, negative effect on arthropod biomass, with no interaction with nutrient availability. Path analysis including all sites implicated nutrient content of the primary producers as a driver of increased arthropod mean size, which we confirmed using 10 sites for which we had foliar nutrient data. Plant biomass and physical structure mediated the increase in arthropod abundance, while the nitrogen treatments accounted for additional variation not explained by our measured plant variables. The mean size of arthropod individuals was 2.5 times more influential on the plot‐level total arthropod biomass than was the number of individuals. The eutrophication of grasslands through human activity, especially nitrogen deposition, thus may contribute to higher production of arthropod consumers through increases in nutrient availability across trophic levels.

Solubility of Tin in Aqueous Media: Implications for Regulatory Ecotoxicity Testing? - Iain Wilson; Adam Peters; Graham Merrington; Jeremy Pearce; Jonathan Rickwood; Paul Cusack; Kay Nimmo (Bulletin of Environmental Contamination and Toxicology, 2017)

By their own devices: invasive Argentine ants have shifted diet without clear aid from symbiotic microbes - Yi Hu; David A. Holway; Piotr Łukasik; Linh Chau; Adam D. Kay; Edward G. LeBrun; Katie A. Miller; Jon G. Sanders; Andrew V. Suarez; Jacob A. Russell (Molecular Ecology, 2017)
The functions and compositions of symbiotic bacterial communities often correlate with host ecology. Yet cause–effect relationships and the order of symbiont vs. host change remain unclear in the face of ancient symbioses and conserved host ecology. Several groups of ants exemplify this challenge, as their low‐nitrogen diets and specialized symbioses appear conserved and ancient. To address whether nitrogen‐provisioning symbionts might be important in the early stages of ant trophic shifts, we studied bacteria from the Argentine ant, Linepithema humile – an invasive species that has transitioned towards greater consumption of sugar‐rich, nitrogen‐poor foods in parts of its introduced range. Bacteria were present at low densities in most L. humile workers, and among those yielding quality 16S rRNA amplicon sequencing data, we found just three symbionts to be common and dominant. Two, a Lactobacillus and an Acetobacteraceae species, were shared between native and introduced populations. The other, a Rickettsia , was found only in two introduced supercolonies. Across an eight‐year period of trophic reduction in one introduced population, we found no change in symbionts, arguing against a relationship between natural dietary change and microbiome composition. Overall, our findings thus argue against major changes in symbiotic bacteria in association with the invasion and trophic shift of L. humile . In addition, genome content from close relatives of the identified symbionts suggests that just one can synthesize most essential amino acids; this bacterium was only modestly abundant in introduced populations, providing little support for a major role of nitrogen‐provisioning symbioses in Argentine ant's dietary shift.

Evidence for extensive but variable nutrient limitation in New Zealand lakes - Amy C. Krist; Adam D. Kay; Elizabeth Scherber; Katelyn Larkin; Bennett J. Brown; Diana Lu; Donald T. Warren; Ruth Riedl; Maurine Neiman (Evolutionary Ecology, 2016)

Thermal adaptation and phosphorus shape thermal performance in an assemblage of rainforest ants - Michael Kaspari; Natalie A. Clay; Jane Lucas; Shai Revzen; Adam Kay; Stephen P. Yanoviak (Ecology, 2016)
We studied the Thermal Performance Curves ( TPC s) of 87 species of rainforest ants and found support for both the Thermal Adaptation and Phosphorus‐Tolerance hypotheses. TPC s relate a fitness proxy (here, worker speed) to environmental temperature. Thermal Adaptation posits that thermal generalists (ants with flatter, broader TPC s) are favored in the hotter, more variable tropical canopy compared to the cooler, less variable litter below. As predicted, species nesting in the forest canopy 1) had running speeds less sensitive to temperature; 2) ran over a greater range of temperatures; and 3) ran at lower maximum speeds. Tradeoffs between tolerance and maximum performance are often invoked for constraining the evolution of thermal generalists. There was no evidence that ant species traded off thermal tolerance for maximum speed, however. Phosphorus‐Tolerance is a second mechanism for generating ectotherms able to tolerate thermal extremes. It posits that ants active at high temperatures invest in P‐rich machinery to buffer their metabolism against thermal extremes. Phosphorus content in ant tissue varied three‐fold, and as predicted, temperature sensitivity was lower and thermal range was higher in P‐rich species. Combined, we show how the vertical distribution of hot and variable vs. cooler and stable microclimates in a single forest contribute to a diversity of TPC s and suggest that a widely varying P stoichiometry among these ants may drive some of these differences.

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

A continent‐wide study reveals clear relationships between regional abiotic conditions and post‐dispersal seed predation - John L. Orrock; Elizabeth T. Borer; Lars A. Brudvig; Jennifer Firn; Andrew S. MacDougall; Brett A. Melbourne; Louie H. Yang; Dirk V. Baker; Avi Bar‐Massada; Michael J. Crawley; Ellen I. Damschen; Kendi F. Davies; et al. (Journal of Biogeography, 2015)
Aim Large‐scale patterns linking energy availability, biological productivity and diversity form a central focus of ecology. Despite evidence that the activity and abundance of animals may be limited by climatic variables associated with regional biological productivity (e.g. mean annual precipitation and annual actual evapotranspiration), it is unclear whether plant–granivore interactions are themselves influenced by these climatic factors across broad spatial extents. We evaluated whether climatic conditions that are known to alter the abundance and activity of granivorous animals also affect rates of seed removal. Location Eleven sites across temperate North America. Methods We used a common protocol to assess the removal of the same seed species ( Avena sativa ) over a 2‐day period. Model selection via the Akaike information criterion was used to determine a set of candidate binomial generalized linear mixed models that evaluated the relationship between local climatic data and post‐dispersal seed predation. Results Annual actual evapotranspiration was the single best predictor of the proportion of seeds removed. Annual actual evapotranspiration and mean annual precipitation were both positively related to mean seed removal and were included in four and three of the top five models, respectively. Annual temperature range was also positively related to seed removal and was an explanatory variable in three of the top four models. Main conclusions Our work provides the first evidence that energy and precipitation, which are known to affect consumer abundance and activity, also translate to strong, predictable patterns of seed predation across a continent. More generally, these findings suggest that future changes in temperature and precipitation could have widespread consequences for plant species composition in grasslands, through impacts on plant recruitment.

Thermal adaptation generates a diversity of thermal limits in a rainforest ant community - Michael Kaspari; Natalie A. Clay; Jane Lucas; Stephen P Yanoviak; Adam Kay (Global Change Biology, 2015)
The Thermal Adaptation Hypothesis posits that the warmer, aseasonal tropics generates populations with higher and narrower thermal limits. It has largely been tested among populations across latitudes. However, considerable thermal heterogeneity exists within ecosystems: across 31 trees in a Panama rainforest, surfaces exposed to sun were 8 °C warmer and varied more in temperature than surfaces in the litter below. Tiny ectotherms are confined to surfaces and are variously submerged in these superheated boundary layer environments. We quantified the surface CT min and CT max s (surface temperatures at which individuals grew torpid and lost motor control, respectively) of 88 ant species from this forest; they ranged in average mass from 0.01 to 57 mg. Larger ants had broader thermal tolerances. Then, for 26 of these species we again tested body CT max s using a thermal dry bath to eliminate boundary layer effects: body size correlations observed previously disappeared. In both experiments, consistent with Thermal Adaptation, CT max s of canopy ants averaged 3.5–5 °C higher than populations that nested in the shade of the understory. We impaled thermocouples in taxidermy mounts to further quantify the factors shaping operative temperatures for four ant species representing the top third (1–30 mg) of the size distribution. Extrapolations suggest the smallest 2/3rds of species reach thermal equilibrium in CT max subsuming 74% of those previously recorded for ant populations worldwide. The Thermal Adaptation Hypothesis can be a powerful tool in predicting diversity of thermal limits within communities. Boundary layer temperatures are likely key to predicting the future of Earth's tiny terrestrial ectotherm populations.

The importance of dissolved N:P ratios on mayfly (Baetis spp.) growth in high-nutrient detritus-based streams - Carrie A. Deans; Spencer T. Behmer; Adam Kay; Neal Voelz (Hydrobiologia, 2015)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

A life history continuum in the males of a Neotropical ant assemblage: refuting the sperm vessel hypothesis - Jonathan Z. Shik; Deana Flatt; Adam Kay; Michael Kaspari (The Science of Nature, 2012)

The effects of modulating eNOS activity and coupling in ischemia/reperfusion (I/R) - Kerry-Anne A. Perkins; Sailesh Pershad; Qian Chen; Sloane McGraw; Jovan S. Adams; Christopher Zambrano; Samuel Krass; Jeffrey Emrich; Brandon Bell; Michael Iyamu; Catherine Prince; Helen Kay; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Estrogen-induced effects on the neuro-mechanics of hopping in humans - Adam L. Bryant; Kay M. Crossley; Simon Bartold; Erik Hohmann; Ross A. Clark (European Journal of Applied Physiology, 2011)

Nutrition and interference competition have interactive effects on the behavior and performance of Argentine ants - Adam D. Kay; Taylor Zumbusch; Justa L. Heinen; Tom C. Marsh; David A. Holway (Ecology, 2010)
Food availability often influences competitive outcomes through effects on consumer growth. Although it has received less attention, food availability may also affect competition through nutritional effects on behavior. One hypothesis linking nutrition and competition in ants posits that increased access to carbohydrates favors greater investment in worker traits that underlie behavioral dominance. We tested this hypothesis by varying dietary protein : carbohydrate (P:C) ratios and levels of interspecific interference for Argentine ants ( Linepithema humile ), a widespread invasive species. As predicted, colonies facing interference increased patrolling more when reared on low P:C diets; this result is the first demonstration of an interactive effect of nutrition and interference on ant colonies. Several results suggest that this dietary effect on patrolling was due primarily to changes in colony size rather than worker behavior. Colonies on lower P:C diets had lower worker mortality and larger final colony sizes. Diet had little effect on per capita patrolling, and worker behavior in performance assays depended more on previous exposure to interference than on diet. Our findings indicate that dietary P:C ratios can influence Argentine ant performance in a competitive environment and suggest a mechanism by which monopolization of carbohydrate‐rich resources can help invasive ants displace native ant competitors.

Mechanisms related to the cardioprotective effects of protein kinase C epsilon (PKC ɛ) peptide activator or inhibitor in rat ischemia/reperfusion injury - Jane Chun-wen Teng; Helen Kay; Qian Chen; Jovan S. Adams; Christopher Grilli; Giuseppe Guglielmello; Christopher Zambrano; Samuel Krass; Adrian Bell; Lindon H. Young (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

LONG‐TERM BURNING INTERACTS WITH HERBIVORY TO SLOW DECOMPOSITION - Adam D. Kay; Josh Mankowski; Sarah E. Hobbie (Ecology, 2008)
Fires can generate spatial variation in trophic interactions such as insect herbivory. If trophic interactions mediated by fire influence nutrient cycling, they could feed back on the more immediate consequences of fire on nutrient dynamics. Here we consider herbivore‐induced effects on oak litter quality and decomposition within a long‐term manipulation of fire frequency in central Minnesota, USA. We focused on bur oak ( Quercus macrocarpa ) trees, which are common across the fire frequency gradient and are often heavily infested with either lace bugs ( Corythuca arcuata ) or aphids ( Hoplochaithropsus quercicola ). We used targeted exclusion to test for herbivore‐specific effects on litter chemistry and subsequent decomposition rates. Lace bug exclusion led to lower lignin concentrations in litterfall and subsequently accelerated decomposition. In contrast, aphid exclusion had no effect on litterfall chemistry or on decomposition rate, despite heavy infestation levels. Effects of lace bug herbivory on litterfall chemistry and decomposition were similar in burned and unburned areas. However, lace bug herbivory was much more common in burned than in unburned areas, whereas aphid herbivory was more common in unburned areas. These results suggest that frequent fires promote oak–herbivore interactions that decelerate decomposition. This effect should amplify other influences of fire that slow nitrogen cycling.

Stoichiometric response of nitrogen-fixing and non-fixing dicots to manipulations of CO2, nitrogen, and diversity - Amy M. Novotny; John D. Schade; Sarah E. Hobbie; Adam D. Kay; Marcia Kyle; Peter B. Reich; James J. Elser (Oecologia, 2007)

Division of foraging labor in ants can mediate demands for food and safety - Adam Kay; Steven W. Rissing (Behavioral Ecology and Sociobiology, 2005)

Stoichiometric relations in an ant‐treehopper mutualism - Adam D. Kay; Sara E. Scott; John D. Schade; Sarah E. Hobbie (Ecology Letters, 2004)
Carbon : nitrogen : phosphorus (C : N : P) stoichiometry can underlie physiological and life history characteristics that shape ecological interactions. Despite its potential importance, there is much to learn about the causes and consequences of stoichiometric variation in terrestrial consumers. Here we show that treehoppers ( Publilia modesta ) tended by ants ( Formica obscuripes ) contained lower N concentrations than treehoppers on plants from which ants were excluded. Ant presence also affected nutrient concentrations in host plants: on plants with ants, leaves contained uniformly low concentrations of N; on plants without ants, N concentrations were low only in the few leaves fed upon by treehoppers at the time of collection. We suggest treehopper feeding reduces leaf nutrient levels and ants positively affect treehopper abundance, producing a top–down effect on plant quality. Determining the causes of these stoichiometric changes should help elucidate factors guiding the dynamics of conditional mutualisms between ants and homopterans.